2011
DOI: 10.1590/s1516-35982011001200044
|View full text |Cite
|
Sign up to set email alerts
|

Behavior patterns of cows with Charolais or Nellore breed predominance fed diets with plant extract or monensin sodium

Abstract: -The objective of this research was to study the ingestive behavior of feedlot cows fed additives based on plant extracts or monensin sodium. Twenty-four Charolais and Nellore crossbred cows with age and average initial weight of 7 years and 423 kg, respectively, were used. The experimental diets were plant extracts: basal diet + 5 g/animal/day of a natural additive composed of 750 mg of essential oil of thyme (Thymus vulgaris), 150 mg of garlic (Allium sativum), 250 mg of rosemary extract (Rosmarimus officina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…Este comportamento também foi observado no trabalho desenvolvido por Castro et al (2009) que utilizaram silagem de milho como fonte de volumoso e suplementação com concentrado, assim como no estudo de Segabinazzi et al (2011), em que os animais consumiram dietas a base de silagem de milho e concentrado na proporção de 40:60, e o restante, e pastagem de milheto. Ambos avaliaram animais em confinamento.…”
Section: Resultados E Discussõesunclassified
“…Este comportamento também foi observado no trabalho desenvolvido por Castro et al (2009) que utilizaram silagem de milho como fonte de volumoso e suplementação com concentrado, assim como no estudo de Segabinazzi et al (2011), em que os animais consumiram dietas a base de silagem de milho e concentrado na proporção de 40:60, e o restante, e pastagem de milheto. Ambos avaliaram animais em confinamento.…”
Section: Resultados E Discussõesunclassified
“…Outros testes do efeito da inclusão de levedura no comportamento ingestivo também não obtiveram diferença significativa para os tempos de ruminação, ócio, alimentação e ingestão de água (SEGABINAZZI et al, 2011;NEUMANN et al, 2013). Porém, Neumann et al (2013) observaram um aumento da frequência de alimentações diárias de animais que consumiam leveduras vivas, sugerindo como possível resposta para este reflexo o aumento na taxa de passagem da dieta pelo trato gastrointestinal.…”
Section: Resultsunclassified
“…Similar to the present study, Ornaghi et al (2017) reported that essential oils did not affect feed intake behavior. Segabinazzi et al (2011) fed a blend (5 g/cow daily) of rosemary and soap tree ( Quillaja saponaria ) extract, thyme and garlic oil to confined cows and found that it had no impact on the number of meals per day. Both studies agree with our finding that DA did not alter feeding behavior.…”
Section: Discussionmentioning
confidence: 99%